BUILDING BRAND RESONANCE: OPTIMIZING SYMBOLIC BRAND REPUTATION AND CUSTOMERS’ EMOTIONAL VALUE - Saputra, Murry Harmawan; Ardyan, Elia; Tanesia, Cindy Yoel; Ariningsih, Endah Pri (UI Scholars Hub, 2021)
Manuscript type: Research Paper Research Aims: The objective of this research is to create a conceptual model that explains how the process of building and increasing brand resonance by constructing important factors regarding consumer perceptions of brands, such as brand love, brand attitude, emotional customer value, and symbolic brand reputation. Design/methodology/approach: The respondents were owners and users of Toyota Fortuner car in Indonesia. There was questionnaires distributed directly to the Toyota Fortuner car users in several big cities in Indonesia (Yogyakarta, Semarang, Bandung, Jakarta, and Surabaya). Research Findings: The acceptance of all proposed hypotheses shows the importance of brand love, brand attitude, emotional customer value, and symbolic brand reputation in increasing the success of building brand resonance, so that the company is able to make customers have a strong bond with the brand. Theoretical Contribution/Originality: The theoretical model of this research could be utilized as an essential reference in developing a brand management model through the CBBE approach. The originality of this research is placed on the new conceptual model development, in order to build a strong brand resonance. Practitioner/Policy Implication: This research has distinctly indicated that there were three methods to drive increased brand resonance that companies could adopt in setting the brand policies. These three important things included increasing the symbolic brand reputation and customers’ emotional value, increasing the positive attitude of customers towards the brand (brand attitude), and increasing the consumer's affection for the brand. Research limitation/Implications: This research utilizes samples on only one automotive brand and company.